Peran Patroli Unit Turjawali Dalam Mencegah Kejahatan Curanmor di Wilayah Hukum Polresta Cirebon - Adityatama Firmansyah (Police Studies Review, 2020)
Crimes of motor vehicle theft are rife in the jurisdiction of Cirebon Police. In the past three years (2017-2019) there has been a crime of fraud which has always increased. In this regard, the role of the Turjawali Unit patrol becomes very important because the activities carried out by the Turjawali Unit will prevent the emergence of intentions and opportunities for perpetrators of fraud so that the implementation of patrol is a preventive effort by the National Police in providing security and peace to the public. Although the Satsabhara Turjawali Cirebon Police Unit has carried out petrol, the crime of motor vehicle theft still occurs in Cirebon Police jurisdiction, this is because there are still limited capabilities of the Turjawali Unit in carrying out patrols and also because the people are less concerned in securing motorized vehicles. Inadequate security results in the appearance of criminal intentions and opportunities for perpetrators to commit crimes. The motivation of perpetrators of motor vehicle theft is generally due to economic reasons. In conducting patrols there are internal and external problems. Internal problems include the limited personnel of the Turjawali Unit Sabhara Unit, no personnel has technical skills because there is no personnel participating in vocational education at FT Sabhara, limited facilities and infrastructure, budget limitations, and the lack of effective patrol methods. While external problems include the level of unemployment of society leads to criminality and lack of public awareness in securing motor vehicles. Matters relating to internal problems are expected to be more optimal and effective when managed properly using the management function theory of George F Terry while external problems are expected to be able to pay close attention to the routine activity theory of Marcus Felson and Robert K.Cohen specifically to prevent crime from occurring theft of motorized vehicles should be undertaken there are 3 (three) elements together which include: 1). Motivated performers. 2). Striking targets are making the attention of victims of crime; 3). The existence of safeguards that can guard over people, goods the target. From the results of the study, the researchers give suggestions, among others: Addition of personnel of the Turjawali Unit, improvement of the technical abilities of patrol members of the Sabhara Unit Turjawali Unit by holding education and training, increasing dialogical patrol programs with 4 wheels and 2 wheels, and increasing cooperation with the community and other agencies. Keywords: Role, Patrol, Prevention of motor vehicle crime, Sabhara